Historical and Cultural Influences on Word Formation in Indonesian and Malagasy - Augustin, Ravaoarisoa Simonette; Emynorane, Ralaivao Hanginiaina (International Journal of Research and Community Empowerment, 2025)
Word formation is the process of creating new words in a language, which can be influenced by historical events, cultural interactions, and contact with other languages. In this context, this study explores the historical and cultural factors that have shaped word formation in Indonesian and Malagasy, two languages from distinct linguistic and cultural contexts. The primary objective is to analyze how historical events, cultural exchanges, and contact with other languages have influenced the development of word formation processes in both languages. This study uses a qualitative approach using a documentation study to gather relevant textual data. Data collection involved reviewing historical records, linguistic texts, and scholarly articles, while data analysis was conducted through thematic analysis to identify patterns and influences on word formation. The findings reveal that both languages exhibit significant historical and cultural influences, such as colonialism and trade, which have contributed to the introduction of loanwords and new word-formation strategies. In conclusion, the study highlights the role of historical and cultural contexts in shaping the evolution of language and provides insights into the interplay between linguistic structures and societal influences in both Indonesian and Malagasy.